2012
DOI: 10.1097/mpa.0b013e31824f3669
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Case-Matched Studies Comparing Open and Laparoscopic Distal Pancreatectomy

Abstract: This study represents the strongest evidence (level 3a) to date that LDPs are a safe operation. However, there is still a need for randomized controlled trials to confirm this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 15 publications
4
75
1
1
Order By: Relevance
“…It is noteworthy that there is a recent trend toward an increased size of the excised lesions (4.0 ± 2.8 cm vs. 3.3 ± 1.5 cm) noted in the literature. [20] Consistent with previous studies, [14,15] our operative time for LDP was longer than for ODP (median 195.5 vs. 112.5 min). Shin et al [22] reported a median operative time of 195 min for LDP, whereas Braga et al [28] reported a median duration of surgery of 239 min for LDP, significantly higher than that for ODP (213 min), but their series included a high rate (30%) of adenocarcinomas.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is noteworthy that there is a recent trend toward an increased size of the excised lesions (4.0 ± 2.8 cm vs. 3.3 ± 1.5 cm) noted in the literature. [20] Consistent with previous studies, [14,15] our operative time for LDP was longer than for ODP (median 195.5 vs. 112.5 min). Shin et al [22] reported a median operative time of 195 min for LDP, whereas Braga et al [28] reported a median duration of surgery of 239 min for LDP, significantly higher than that for ODP (213 min), but their series included a high rate (30%) of adenocarcinomas.…”
Section: Discussionsupporting
confidence: 80%
“…[5] More recently, several studies and meta-analyses have shown that LDP is a safe procedure, with improved outcomes and reduced hospital stays. [13][14][15][16] Cao et al [12] in their population-based retrospective cohort study reported a reduction of 1.22 days in LoS associated with minimally invasive surgery, with no differences in the perioperative mortality and total hospital costs. Furthermore, lower rates of infectious complications (30.1% vs. 39%) and bleeding complications (13.1% vs. 20.6%) were reported in LDP vs. ODP.…”
Section: Discussionmentioning
confidence: 99%
“…LDP has rapidly expanded its application over the last decade and, although randomized studies are lacking, recent meta-analyses [2][3][4][5] have suggested that LDP was safe and effective as open distal pancreatectomy. Nevertheless, Rosales-Velderrain et al [6] have reported that, in the United States, only a low percentage (15%-27%) of patients with body/tail pancreatic tumors were subjected to LDP.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Recent systematic reviews and meta-analyses [2][3][4][5] have demonstrated the safety and feasibility of LDP for benign and malignant pancreatic lesions and have reported postoperative outcome advantages with respect to an open approach.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the standardization of the technique. Based on the available data, laparoscopic distal pancreatectomy have adequate safety profiles, equivalent or better perioperative outcomes, and noninferior oncologic outcomes (4)(5)(6)14) .…”
Section: Discussionmentioning
confidence: 99%